PEGylated magnetic nanographene oxide for targeted delivery of arsenic trioxide and sec-o-glucosylhamaudol in tumor treatment with improved dual-drugs synergistic effect - Jinlai Cheng; Kun Hong; Jianhui Sun; Hongmei Li; Yu Zhao; Qinghe Zhao; Yuqing Tan; Miyi Yang (SpringerOpen, 2023)
Abstract Arsenic trioxide (ATO) is a promising chemotherapeutic agent, but its clinical application is limited due to its poor pharmacokinetics and dose-limited toxicity. Moreover, the combination of ATO and sec-o-glucosylhamaudol (SOG) can improve the therapeutic effect of hepatoma. In this study, PEGylated magnetic nanographene oxide (PEG@MGO) was used as magnetic carriers to enhance the targeting ability of the drug delivery system. ATO and SOG are loaded on the surface of PEG@MGO nanoparticles through electrostatic interactions. This biocompatible nanocomposite shows magnetic susceptibility, pH sensitivity, and high loading capacity of the drugs. The in vitro cytotoxicity study of human hepatoma cell line (HepG2) cells showed more significant cytotoxicity and obvious synergistic effect between ATO and SOG compared with that of single drug-loaded nanoparticles via MTT assay. In vitro cellular uptake was observed by Prussian blue staining and fluorescently labeling. The results demonstrated a high cellular internalization rate of PEG@MGO. The ATO and SOG co-loaded nanodrug significantly inhibits the growth of tumors in vivo, which might be due to the oxidative stress and proapoptotic effect. This type of multidrug nanocomposite offers a promising alternative for cancer therapy. Graphical Abstract A pH-sensitive polyethylene glycol-modified magnetic graphene oxide loaded with ATO and SOG (PEG@MGO@ATO + SOG) was prepared for the magnetically targeted and efficient synergistic-chemo cancer therapy, which exhibited high specificity and good biocompatibility.